Networking banana and plantain: INIBAP Annual Report 1996 - International Network for the Improvement of Banana and Plantain (1997)
Summary French and Spanish This report contains focus papers on 3 aspects: (1) Complementary conservation; (2) Molecular marker-assisted analysis of the Musa genome complex; and (3) Uses of Musa. The thematic activities reported include Musa germplasm management and improvement. There are also reports of INIBAP's activities in (1) Latin America and the Caribbean, (2) Asia and the Pacific, and (3) sub-saharan Africa. (Abstract © CAB ABSTRACTS, CAB International)